Physiotherapist's approach and treatment preference in the patients of rheumatoid arthritis in Karachi, Pakistan: A cross sectional survey - Shobha Lekhraj; Vikash Chughani; Natasha Bhutto; Aadil Ameer Ali (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
Objective: To assess the treatment approach of physiotherapists towards patients with Rheumatoid Arthritis. Material & methods: A cross-sectional study was conducted from June to August 2016 among the 116 selected participants who were working in different physical therapy setups of Karachi Pakistan. A self-constructed questionnaire was used among the participants which consist of demographic Characteristics (age, gender, Qualification, and experience). While the Knowledge and utilization related close-ended questions were the 1. Type of exercise (isometrics and isotonic exercise), utilization of manual techniques (use of Maitland peripheral joint mobilization techniques, Cyrix mobilization techniques, Mulligan mobilization techniques & Manual joint distraction). 2. The use of electrotherapy modalities (use of TENS, Ultrasound, Cryotherapy & Heating) & 3. Treatment preference includes (results of manual therapy, electrotherapy or electrotherapy & manual therapy both in combination). Data were analyzed by using Statistical Package for Social Sciences (SPSS) version 21.  Results: The majority of physiotherapists (n=71, 61.2%) belong to the age group of 31 to 45 years, and (n=71, 61.2%) were male. After checking the Qualification the majority (n=65, 56%) were Post-graduate and (n=62, 53.2%) were having 7 to 15 years of experience. Among all (n=94, 81%) of physiotherapists were using an isometric type of exercises in the patients with Rheumatoid arthritis. Most of (n=101, 87%) the Physiotherapist was using peripheral joint distraction in patients with Rheumatoid arthritis. The majority (n=109, 93.9%) of physiotherapists were using manual therapy and electrophysical agents in combination among the patients with Rheumatoid arthritis. Conclusion: The physiotherapists who are working in different setups of Karachi were treating the patients of RA by using different techniques of manual therapy along with the combination of electrophysical agents. In electrophysical agents, they were using the tens and heating combination for pain management.